Self-induced Intravesical Foreign Body: An Unusual Case Report - Shah, Amit Kumar; Verma, Sumit; Baskota, Bashu Dev (Medical Journal of Eastern Nepal, 2025)
Foreign bodies get into the bladder by self-insertion, migration, or as a part of iatrogenic and the penetrating injuries. Most common cause of self-insertion is for the masturbation pleasure. The diagnosis and the proper management can be difficult especially when the foreign body is radiolucent. Commonly patient can present with lower urinary tract symptoms. In very rare case patient comes and tells admits self-insertion of foreign body has been performed. The removal of the Intravesical foreign body still today remains a challenge for the urologist; removal of the foreign body without any injury to the bladder or the urethra gives good outcome.